Nieobecnienie. Historie (o) śmierci - Żychliński, Arkadiusz (Wydawnictwo Naukowe UAM, 2011)
One of the last great novels of José Saramago, Death with Interruptions, begins with an epigraph taken from Ludwig Wittgenstein: “If, for example, you were to think more deeply about death, then it would be truly strange if, in so doing, you did not encounter new images, new linguistic fields”. The aim of my paper is to ponder on what kind of a new language game the Portuguese writer is offering us in his book and how to interpret his investigations from the angle of another contemporary literary and philosophical thanatological discourses.
Extinction. Histories of death